Inhaled Glucocoriticoids in Children: A Facourable Therapeutic Index - F Estelle R Simons (Canadian Respiratory Journal)
In children with persistent asthma, inhaled glucocorticoids decrease symptoms and exacerbations, decrease the need for rescue bronchodilator medications, improve airway patency and reduce airway hyperresponsiveness. When administered in the lowest doses that prevent symptoms and eliminate the need for supplemental courses of oral glucocorticoids, they are unlikely to cause clinically important systemic adverse events. Inhaled glucocorticoids have a favourable risk to benefit ratio in this population.